Morita therapy for depression and anxiety (Morita Trial): study protocol for a pilot randomised controlled trial - Sugg, Holly Victoria Rose (Trials, 2016)
BACKGROUND: Morita Therapy, a psychological therapy for common mental health problems, is in sharp contrast to established western psychotherapeutic approaches in teaching that undesired symptoms are natural features of human emotion rather than something to control or eliminate. The approach is widely practiced in Japan, but untested and little known in the UK. A clinical trial of Morita Therapy is required to establish the effectiveness of Morita Therapy for a UK population. However, a number of methodological, procedural and clinical uncertainties associated with such a trial first require addressing. METHODS/DESIGN: The Morita Trial is a mixed methods study addressing the uncertainties associated with an evaluation of Morita Therapy compared with treatment as usual for depression and anxiety. We will undertake a pilot randomised controlled trial with embedded qualitative study. Sixty participants with major depressive disorder, with or without anxiety disorders, will be recruited predominantly from General Practice record searches and randomised to receive Morita Therapy plus treatment as usual or treatment as usual alone. Morita Therapy will be delivered by accredited psychological therapists. We will collect quantitative data on depressive symptoms, general anxiety, attitudes and quality of life at baseline and four month follow-up to inform future sample size calculations; and rates of recruitment, retention and treatment adherence to assess feasibility. We will undertake qualitative interviews in parallel with the trial, to explore people’s views of Morita Therapy. We will conduct separate and integrated analyses on the quantitative and qualitative data. DISCUSSION: The outcomes of this study will prepare the ground for the design and conduct of a fully-powered evaluation of Morita Therapy plus treatment as usual versus treatment as usual alone, or inform a conclusion that such a trial is not feasible and/or appropriate. We will obtain a more comprehensive understanding of these issues than would be possible from either a quantitative or qualitative approach alone. TRIAL REGISTRATION: Current Controlled Trials ISRCTN17544090 registered on 23 July 2015. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-016-1279-3) contains supplementary material, which is available to authorized users.